Feasibility of therapeutic Chinese massage (tui na) for peripheral neuropathy among people with human immunodeficiency virus: findings of a pilot randomized controlled trial - Ge, Song; Dune, Linda; Liu, Minhui; Fu, Guojing; Ma, Haixia; Hu, Jiale; Lin, Xuechun; Li, Junxin (Frontiers in Neurology, 2023)
Background Peripheral neuropathy (PN) is prevalent in people with human immunodeficiency virus (PHIV) with no Food and Drug Administration-approved treatment. Therapeutic Chinese massage (TCM) is a promising noninvasive and non-harmful intervention for HIV-related PN. However, relevant research is lacking. The purpose of this study is to evaluate the feasibility of TCM for HIV-related PN. Method We conducted a pilot, single-centered, two-arm, double-blinded, randomized controlled trial. Twenty eligible PHIV were recruited primarily from the AIDS Foundation Houston, Inc. in Texas and were randomly assigned into two groups. Ten participants in the intervention group received three weekly 25-min TCM sessions by a certified TCM therapist. The remaining ten control group participants received the same therapist’s three weekly 25-min placebo massage sessions on their lower extremities. The outcome was the feasibility of this study as measured by recruitment and completion rates, participant safety, and treatment adherence and compliance, as well as the effect size of the intervention. Results The study population comprised 20 PHIV (mean age 55.23). This study showed high feasibility as measured by a high rate of recruitment, a 100% rate of completion, and zero serious adverse events. As we inquired 21 respondents for eligibility for the study, all except one had HIV-related PN. All respondents were willing to participate in the study and adhered to the group assignment after they enrolled in the study. The participants’ baseline pain was at a medium to a high level (6.30 [2.15] out of 10). Conclusion Chinese massage is a feasible intervention in PHIV. Future relevant randomized controlled trials are expected. Clinical trial registration https://clinicaltrials.gov/, NCT05379140.